PENDIDIKAN VOKASI SEBAGAI PILAR PENDIDIKAN TINGGI YANG RESPONSIF DI ERA INDUSTRI 4.0 INDONESIA EMAS 2045: MEMBANGUN KESADARAN GENERASI MUDA KONAWE - Simanjuntak, Raja Agung Hasudungan; Darwis, Mardis; Wardani, Ayu; Rahman, La; Badia, Bahdin Ahad; Aji, Angga Asteriasti; Putra, Fachrizal Cesar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service activity aimed to raise awareness among youth in Konawe Regency about the importance of vocational education as a practical and industry-relevant higher education pathway in the era of Industry 4.0 towards Golden Indonesia 2045. The implementation involved identifying information needs, preparing outreach materials, coordinating with target schools, conducting on-site socialization, and evaluating outcomes through questionnaires. The results revealed improved understanding and interest in vocational education, a shift in perceptions, and increased recognition of local vocational institutions. This program also bridged the information gap and strengthened connections between schools and vocational institutions. The activity effectively encouraged youth participation in vocational education as a strategy to develop competitive human resources in Konawe.